Letter from [Weitz?] to James Curtis Booth (1863)
Mentions a proposed move to Washington, D.C. “unless the rebels take possession of the place.”
Keywords: Booth, James Curtis, 1810-1888; United States Mint; Mint of the United States; American Civil War (United States : 1861-1865)